The verso book of dissent : from Spartacus to the Shoe-Thrower of Baghdad - Hsiao, Andrew; Lim, Audrea (Verso, 2010)
Across the ages and in every continent, people have struggled against those in power and raised their voices in protest-and this unrivalled compendium brings many of them together. From primitive communism in Ancient Greece and Persia, and the Hundred Schools of Thought in Ancient China, via the dissident poets and philosophers of Islam and Judaism, to Galileo, Spinoza, and Giordano Bruno in the Middle Ages, through to the makers of the Dutch and English revolutions in the sixteenth and seventeenth centuries, and then the activists and theorists of the French, American, Haitian, Russian, and Chinese revolutions: Olympe de Gouges, John Brown and Frederick Douglass, Toussaint L'Ouverture, Mandelstam, Lu Hsun, and many more. More recently, Eugene Debs, Joe Hill, the Chicago Martyrs, Bhagat Singh and Muntazer al-Zaidi have fought back against oppressive regimes. This anthology, global in scope, presents the voices of dissent through the ages: poems and songs, pamphlets and speeches, plays and manifestos. The Verso Book of Dissent will become an invaluable tool, reminding today's citizens that these traditions will never die.